Nuove traiettorie del denaro Per una sociologia delle pratiche monetarie - Lazzer, Gian Paolo (Strutture e culture sociali - Open Access, 2018)
After theoretically framing the subject of money, starting from the Philosophy of Money by Georg Simmel and the most recent contributions about sociology of money, the volume proposes a framework of study based on practice theory, with the aim of answering two questions of deep sociological and methodological interest: what money really is and how it is studied.